The coupling of a high-efficiency aerosol collector with electrospray ionisation–Orbitrap mass spectrometry as a novel tool for real-time chemical characterisation of fine and ultrafine particles - Y.-S. Lau; Z. Ristovski; B. Miljevic (Atmospheric Measurement Techniques)
The chemical properties of aerosols in the atmosphere significantly influence their impact on the global climate forcing and human health. However, a real-time molecular-level characterisation of aerosols remains challenging due to the complex nature of their chemical composition. The current study constructed an instrumental system for the real-time chemical characterisation of aerosol particles. The proposed setup consists of a custom-built high-efficiency aerosol collector (HEAC) used to collect aerosol samples into a working fluid and an electrospray ionisation (ESI) Orbitrap mass spectrometer (MS) for the subsequent chemical analysis of the liquid sample. The HEAC/ESI-Orbitrap-MS was calibrated against six chemical compounds – vanillic acid (VA), adonitol, erythritol, tricarballylic acid (TCA), sucrose, and trehalose – to investigate the system's sensitivity and limit of detection (LOD). Results showed that the coupled system has high sensitivities to the tested chemical compounds and a similar, if not better, LOD than other related instrumental techniques. The 3σ LOD of the tested compounds ranged from 1.1 ± 0.14 ng m−3 (erythritol) to 65 ± 7.4 ng m−3 (TCA). The capability of the HEAC/ESI-Orbitrap-MS system to identify the chemical composition of organic aerosols (OAs) was also examined. Sample OA was generated by α-pinene ozonolysis, and the chemical characterisation results were compared to similar studies. Our data showed that the HEAC/ESI-Orbitrap-MS system can identify most of the α-pinene ozonolysis products reported in the literature, including cis-pinonic acid, pinalic acid, and 3-methyl-1,2,3-butanetricarboxylic acid (MBTCA). Monomeric and dimeric reaction products were accurately identified in the mass spectra, even at a total OA mass concentration < 2 µg m−3. The present study showed that the HEAC/ESI-Orbitrap-MS system is a robust technique for the real-time chemical characterisation of OA particles under atmospherically relevant conditions.